2002
DOI: 10.1783/147118902101196063
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the levonorgestrel intrauterine system in treating menorrhagia: Actualities and ambiguities

Abstract: Objective. To review the literature on usage of the levonorgestrel intrauterine system (LNG IUS) An observational study and isolated reports of women with adenomyosis report significant symptomatic relief in these women. Conclusion. Available data refute the notion that uterine enlargement is a contraindication to insertion of the LNG IUS, but there appear to be reasons for a cautious approach when dealing with pathological uteri. IntroductionThe levonorgestrel intrauterine system (LNG IUS: Mirena ® , Scheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The observations that the local release of levonorgestrel in the uterine cavity can cause regression of adenomyosis is further evidence that these lesions can respond to high intrauterine doses of progestins by reducing proliferation and augmenting apoptosis in a similar way to that occurring in the eutopic endometrium [6,14,15]. This is in agreement with our findings that the presence of Mirena in the uterine cavity decreases proliferation and bcl-2 expression in adenomyosis more efficiently than oral contraceptive pills, which were able effectively to reduce proliferation but not bcl-2 expression.…”
Section: Discussionmentioning
confidence: 96%
“…The observations that the local release of levonorgestrel in the uterine cavity can cause regression of adenomyosis is further evidence that these lesions can respond to high intrauterine doses of progestins by reducing proliferation and augmenting apoptosis in a similar way to that occurring in the eutopic endometrium [6,14,15]. This is in agreement with our findings that the presence of Mirena in the uterine cavity decreases proliferation and bcl-2 expression in adenomyosis more efficiently than oral contraceptive pills, which were able effectively to reduce proliferation but not bcl-2 expression.…”
Section: Discussionmentioning
confidence: 96%
“…The use of a levonorgestrel intrauterine device (LNG-IUS) has been associated with a reduction in menstrual blood loss in women with uterine myomas, but its effect on the size of uterine myoma is still debated 8. LNG-IUS is contraindicated in the case of fibroid-associated severe distortion of the uterine cavity (LNG-IUS SmPC), because of the high expulsion rate 810…”
Section: Pharmacological Management Of Uterine Fibroidsmentioning
confidence: 99%
“…There is some evidence that expulsion rates may be increased in the presence of submucous fibroids. [17] Recently, Kriplani et al . reported that use of the LNG-IUS appears to lead to a significant reduction in the uterine volume of women with menorrhagia, as well as reducing the MBL in women with uterine leiomyomas.…”
Section: What About Menorrhagia Due To Pathological Uterine Lesions?mentioning
confidence: 99%